Independence of Learning and Achievement of Learners' Cognitive Abilities in Thermochemical Materials through the Application of Flipped Classroom - Ruhul Mukhlisa; Abdul Gani; Sri Winarni; Ibnu Khaldun; Latifah Hanum (Postgraduate, University of Mataram, 2021)
The utilization of online media such as learning videos, e-books, e-libraries, and virtual laboratories as a source of independent learning by learners is still very low, as a result of which teachers are still the main source of learning. This shows the low independence of learning learners, even though independence is one-factor affecting learning achievement. The correct learning methods can increase the independence of learning learners, one of which is by applying flipped classrooms. This research aims to find out the effect of the application of flipped classrooms on learning independence and cognitive achievement of learners in thermochemical materials as well as the correlation of learning independence with the achievement of cognitive abilities of learners. This study is an experimental study with the design of two groups at random. The measuring instrument used is a matter of postest and learning independence questionnaire. The research data were analyzed using the SPSS for Windows program. The results found that learning independence and better achievement of cognitive abilities were shown in the group that applied the class upside down. There was a significant positive relationship between the achievement of cognitive ability and the independence of learning in both groups, both in classes that applied classes in reverse and in classes that did not apply inverse classes.